Determinant of Mother’s Role in Feeding Practice Among Stunted Children - Sutarji Sutarji; Apriyani Puji Hastuti; Bagus Dadang Prasetiyo (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2025)
Background Stunted children require a varied diet, with gradually increasing quantity, consistent food intake, and a balanced macro-micro nutrient ratio. The mother's role in child feeding practices is crucial. The purpose of this study was to examine factors related to the mother's role in feeding stunted children aged 6-24 months. Methods A case-control study involving children aged 6-24 months was conducted. A sample size of 180 children was selected using a stratified random sampling procedure. The research instrument used a questionnaire that had been tested for validity and reliability, with data analysis using linear regression using SPSS 16.0 statistical software. Results Factors related to the mother's role in feeding stunted children based on nutritional status are age, education level, occupation, motivation, mobility, decision making, knowledge, self-esteem, self-efficacy, family type, family role, family stress, family coping, family social support, birth weight, food preparation, and responsive feeding. All of these factors can influence the mother's role in feeding stunted children based on nutritional status with a p value <0.005. Meanwhile, the child's age, birth length, breastfeeding, and child feeding are not factors related to the mother's role in feeding stunted children based on nutritional status.